Effect of LaAlO3-supported modified Ni-based catalysts on aqueous phase reforming of glycerol - Park, Yoon Hwa; Kim, Ji Yeon; Moon, Dong Ju; Park, Nam Cook; Kim, Young Chul (SPRINGER, 2015)
The present study investigates the catalytic performance over Ni-based catalysts supported on LaAlO3 perovskite for aqueous phase reforming of glycerol to produce hydrogen. The X-Ni/LaAlO3 (X = Cu, Co, Fe) catalysts were prepared by precipitation. The amount of added Cu, Fe, and Co in the Ni/LaAlO3 catalyst was fixed at 5 wt.%. The catalytic reaction was tested at 250 A degrees C and 20 bar with a reactant feed of 15 wt.% aqueous glycerol solution (5 mL/h). The modified Ni/LaAlO3 catalysts were characterized by Brunauer-Emmett-Teller surface area analysis, X-ray diffraction, H-2-temperature programmed reduction, H-2-chemisorption, X-ray photoelectron spectroscopy, and transmission electron microscopy. The morphology and carbon deposition of used catalysts were examined by scanning electron microscopy and thermo-gravimetric analysis, respectively. The Cu-Ni/LaAlO3 catalyst showed the highest glycerol conversion and hydrogen selectivity, a result attributed to the synergistic effect of the nickel and copper components in the catalyst. The small size and high dispersion of Ni particles and suppressed carbon deposition in the Cu-Ni/LaAlO3 catalyst positively influenced its catalytic performance.
Keywords: HYDROGEN-PRODUCTION; RENEWABLE HYDROGEN; STEAM; PEROVSKITE; PROPANE; ETHANOL; OXIDES